PENGARUH INDEKS MASSA TUBUH, USIA MENARCHE DAN STATUS MENSTRUASI TERHADAP MIOMA UTERI - Ulfah, Mariah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Uterine myoma is a common reproductive disorder in women. This case is rarely found at an age that has not been reproduced or not menarche. The growth of uterine myoma is strongly influenced by reproductive hormones, and only manifests during reproductive age. In addition, risk factors for uterine myomas occur in overweight women (obese) who have no offspring and are not married. One prospective study found that the likelihood of uterine myoma risk was as high as 21% for every 10kg increase in body weight, in addition to uterine myoma having maximum growth during reproduction. The result of this research with Chi squere test obtained p value 0.033 which means that pâ‰¤0,05, meaning there is influence between IMT with occurrence of mioma uteri, then p value 0,789 meaning that p> 0,05, so there is no influence of age of menarche with occurrence of uterine myoma, and p value 0.07 which means that p> 0,05, no effect of menstrual status with uterine myoma. Conclusion: 1) The highest body mass index (53.2%) with normal status, (25.5%) was obese type 1, obesity (11.7%), overweight (7.4%), and the lowest was lean (2.1%). 2) The highest menarche incidence (85.1%) of menarche is age 10-16 years, then 11.7% age <10 years, and 3.2% age> 16 years. Menstruation Status picture that 86.2% is still menstruating and 13.8% have not experienced menstruation. 3) There is a relationship between BMI with occurrence of uterine myoma. 4) there is no correlation between age of menarche and occurrence of uterine myoma. 5) There is no relationship between menstrual state and occurrence of uterine myoma. Keywords: uterine myoma, body mass index, menstruation, menarche